Fiscal Policy and Balance of Payments in Nigeria - Etim, Inimino, Edet; Akpanabba, Brown, Uduakobong; Paul, Otubu, Osaretin (Asian Journal of Economics and Empirical Research, 2020)
This study investigated the effect of fiscal policy on balance of payments in Nigeria. The data for the study were obtained from the statistical bulletin of Nigeria’s apex bank spanning 1980 to 2017. The study employed Augmented Dickey-Fuller (ADF) and Autoregressive Distributed Lag (ARDL) Bounds techniques. The result of the ADF test revealed that the variables were stable at order one and zero. The ARDL results showed that in the long run, corporate income tax, government capital expenditure and external debt have positive and significant effect on Nigeria’s balance of payments. Meanwhile, exchange rate has a negative and significant effect on balance of payments in Nigeria. It also revealed that in the short run, corporate income tax and government capital expenditure have positive and significant effect on balance of payments in Nigeria. However, exchange rate and external debt have negative and significant effect on balance of payments in Nigeria. Therefore, this study concluded that fiscal policy has a meaningful effect on Nigeria’s balance of payments during the period of study. This means that fiscal policy is effective in achieving a satisfactory balance of payments in the country.